Leaf chlorophyll parameters and photosynthetic characteristic variations with stand age in a typical desert species (Haloxylon ammodendron) - He, Xiao-hui; Si, Jian-hua; Zhou, Dong-meng; Wang, Chun-lin; Zhao, Chun-yan; Jia, Bing; Qin, Jie; Zhu, Xing-lin (Frontiers in Plant Science, 2022)
As a desert shrub, Haloxylon ammodendron combines ecological, economic, and social benefits and plays an important role in the ecological conservation of arid desert areas. Understanding its physiological characteristics and its mechanism of light energy utilization is important for the conservation and utilization of H. ammodendron. Therefore, we selected five stands (5-, 11-, 22-, 34-, and 46-year-old) of H. ammodendron as research objects in the study and measured their photosynthetic light response curves by a portable open photosynthesis system (Li-6400) with a red-blue light source (6400-02B). Then, we measured the leaf chlorophyll parameters in the laboratory, calculated the photosynthetic characteristics by using Ye Zipiao’s photosynthetic model, analyzed their variation patterns across stand ages, and explored the relationships between leaf chlorophyll parameters and photosynthetic characteristics. The results showed that leaf chlorophyll parameters and photosynthetic characteristics of H. ammodendron at different stand ages were significantly different. Chl content, Pnmax, and LUEmax of H. ammodendron were V-shaped with the increase of stand age. The 5-year-old H. ammodendron was in the rapid growth period, synthesized more Chl a+b content (8.47 mg g−1) only by using a narrower range of light, and the Pnmax and LUEmax were the highest with values of 36.21 μmol m−2 s−1 and 0.0344, respectively. For the 22-year-old H. ammodendron, due to environmental stress, the values of Chl a+b content, Pnmax, and LUEmax were the smallest and were 2.64 mg g−1, 25.73 μmol m−2 s−1, and 0.0264, respectively. For the older H. ammodendron, its Chl content, Pnmax, and LUEmax were not significantly different and tended to stabilize but were slightly higher than those of the middle-aged H. ammodendron. On the other hand, the other photosynthetic parameters did not show significant variation patterns with stand age, such as Rd, AQE, LSP, LCP, and IL-sat. In addition, we found that the relationships between Chl a+b content and Pnmax and between Chl a+b content and LUEmax were highly correlated, except for the older H. ammodendron. Thus, using leaf chlorophyll content as a proxy for photosynthetic capacity and light use efficiency should be considered with caution. This work will provide a scientific reference for the sustainable management of desert ecosystems and vegetation restoration in sandy areas.